Tax Policy, Corporate Saving and Investment Behaviour in Britain - Feldstein, M. S.; Flemming, J. S. (Review of Economic Studies, 1971)
Journal Article Tax Policy, Corporate Saving and Investment Behaviour in Britain Get access M. S. Feldstein, M. S. Feldstein Harvard University Search for other works by this author on: Oxford Academic Google Scholar J. S. Flemming J. S. Flemming Nuffield College, Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 4, October 1971, Pages 415–434, https://doi.org/10.2307/2296687 Published: 01 October 1971